A new species of armored scale, Fiorinia yongxingensis (Hemiptera: Coccomorpha: Diaspididae) from Hainan Province, China - Liu, Di; Cai, Bo; Feng, Jinian (Zootaxa, 2020)
The adult female, adult male and all immature stages (except the male prepupa and pupa) of a new species of Fiorinia (Hemiptera: Coccomorpha: Diaspididae), F. yongxingensis Liu, Cai & Feng sp. n., collected from Hainan Province, China, are described and illustrated. A key is provided to identify the Fiorinia species known to occur in Hainan Province, China. The new species may become a significant pest on coconut palms.